2016
DOI: 10.2183/pjab.92.436
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 protects pancreatic β-cells from oxidative stress by a Nrf2-induced increase in catalase expression and activity

Abstract: Due to intrinsically low levels of antioxidant enzyme expression and activity, insulin producing pancreatic β-cells are particularly susceptible to free radical attack. In diabetes mellitus, which is accompanied by high levels of oxidative stress, this feature of β-cells significantly contributes to their damage and dysfunction. In light of the documented pro-survival effect of chemokine C-X-C Ligand 12 (CXCL12) on pancreatic β-cells, we examined its potential role in antioxidant protection. We report that CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 64 publications
(70 reference statements)
2
18
0
1
Order By: Relevance
“…Biochemical experiments indicated that knockdown of NRF2 could increase MDA concentration and decrease concentration of SOD, GSH and CAT, enhancing the effects of laminarin in MRC-5 cells. Numerous studies have proved the protective role of NRF2 against oxidation in various cell types, keratinocytes ( Madduma Hewage et al, 2016 ; Zheng et al, 2014 ), pancreatic β-cells ( Dinić et al, 2016 ), mesenchymal stem cells ( Loseva et al, 2012 ), amongst others, elevating SOD, GSH and CAT cellular concentration. Besides, up-regulation of NRF2 was accompanied with suppressed MDA level during the amelioration of oxidative damage ( Xie et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical experiments indicated that knockdown of NRF2 could increase MDA concentration and decrease concentration of SOD, GSH and CAT, enhancing the effects of laminarin in MRC-5 cells. Numerous studies have proved the protective role of NRF2 against oxidation in various cell types, keratinocytes ( Madduma Hewage et al, 2016 ; Zheng et al, 2014 ), pancreatic β-cells ( Dinić et al, 2016 ), mesenchymal stem cells ( Loseva et al, 2012 ), amongst others, elevating SOD, GSH and CAT cellular concentration. Besides, up-regulation of NRF2 was accompanied with suppressed MDA level during the amelioration of oxidative damage ( Xie et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12 reduced inflammation in experimental autoimmune encephalomyelitis 38 . It protected b cells from death by promoting islet neovascularization, reduced oxidative stress, and increased cell survival in allogeneic and xenogeneic islet transplantation models [39][40][41][42] . Therefore, the significantly decreased CCL23 and increased CXCL12 levels observed in the CO group in our study suggested less inflammation in CO islets posttransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, after viral infection, ROS are produced from activated phagocytes [24], and they mediate cellular injury and activate inflammatory redox-dependent transcription factors, such as NF-κB, thereby perpetuating inflammation. The virus-mediated production of ROS or a reduction in an- tioxidants can have severe consequences, as β cells are more prone to oxidative damage than most other tissues [8]. Additionally, in T1D, the T cell-mediated autoimmune destruction of pancreatic β cells is secondary to the primary invasion by macrophages and dendritic cells into the islets.…”
Section: Discussionmentioning
confidence: 99%
“…Islets inherently contain only a fraction of enzymatic activity in comparison to the liver, which has the highest abundance of these enzymes [27]. However, β cells are particularly sensitive to ROS because they are low in free radical-quenching (antioxidant) enzymes such as CAT, GPx, and SOD [8]. Thus, the capability of oxidative stress to damage mitochondria and ultimately decrease insulin secretion is not surprising [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation